Globalisation effect measure via hierarchical dynamic factor modelling - Agne Reklaite (Institute of Economic Research (IER), 2015)
In this paper the issue of globalisation and deteriorating precision of domestically oriented frameworks is addressed. A hypothesis that the effect of international trends on the growth of economy is increasing over time is formed. In order to validate this a method of composing foreign series with local indicators in a hierarchical dynamic factor model is presented. The novelty of this approach is that globalisation effect is measured focusing on prediction rather than similarity. This way the measure presents country's sensitivity to global shocks and reveals how much focal country's economy is intertwined with global economy. The application was performed on Lithuanian data and the hypothesis was validated. The results indicate that globalisation effect has an increasing effect over time.
Keywords: C43; E32; C10; 330; leading indicator; hierarchical dynamic factor model; globalisation; economic growth